I'm Hungry, Let's Cook : Fun Food for Kids to Make - Newell, Joanne; Illustrated by Taylor, Chris Roy (Australia The Five Mile Press Pty Ltd, 2008)
"Easy fun food for kids to make."--Provided by publisher.
Include colour illustrations and index
Keywords: Cooking